Physical, mechanical, and morphological properties of hybrid Cytostachys renda/kenaf fiber reinforced with multi-walled carbon nanotubes MWCNT-phenolic composites - Loganathan, Tamil Moli; Hameed Sultan, Mohamed Thariq; Jawaid, Mohammad; Ahsan, Qumrul; Naveen, Jesuarockiam; Md Shah, Ain Umaira; Abu Talib, Abd. Rahim; Basri, Adi Azriff (MDPI AG, 2021)
Adequate awareness of sustainable materials and eco-legislation have inspired researchers to identify alternative sustainable and green composites for synthetic fiber-reinforced polymer composites in the automotive and aircraft industries. This research focused on investigating the physical, mechanical, and morphological properties of different hybrid Cyrtostachys renda (CR)/kenaf fiber (K) (10C:0K, 7C:3K, 5C:5K, 3C:7K, 0C:10K) reinforced with 0.5 wt% MWCNT–phenolic composites. We incorporated 0.5 wt% of MWCNT into phenolic resin (powder) using a ball milling process for 25 h to achieve homogeneous distribution. The results revealed that CR fiber composites showed higher voids content (12.23%) than pure kenaf fiber composites (6.57%). CR fiber phenolic composite was more stable to the swelling tendency, resulting in the lowest percentage of swelling rate (4.11%) compared to kenaf composite (5.29%). The addition of kenaf fiber into CR composites had improved the tensile, flexural, and impact properties. The highest tensile and flexural properties were found for weight fraction of CR and kenaf fiber at 5C:5K (47.96 MPa) and 3C:7K (90.89 MPa) composites, respectively. In contrast, the highest impact properties were obtained for 0C:10K composites (9.56 kJ/m2). Based on the FE-SEM image, the CR fiber lumen was larger in comparison to kenaf fiber. The lumen of CR fiber was attributed to higher void and water absorption, lower mechanical properties compared to kenaf fiber. 5C:5K composite was selected as an optimal hybrid composite, based on the TOPSIS method. This hybrid composite can be used as an interior component (non-load-bearing structures) in the aviation and automotive sectors.